2013
DOI: 10.1038/nnano.2013.208
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping and manipulation of nanostructures

Abstract: Optical trapping and manipulation of micrometre-sized particles was first reported in 1970. Since then, it has been successfully implemented in two size ranges: the subnanometre scale, where light-matter mechanical coupling enables cooling of atoms, ions and molecules, and the micrometre scale, where the momentum transfer resulting from light scattering allows manipulation of microscopic objects such as cells. But it has been difficult to apply these techniques to the intermediate - nanoscale - range that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
670
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 908 publications
(696 citation statements)
references
References 173 publications
0
670
1
4
Order By: Relevance
“…Up to now, optical tweezing has been exploited as one of the most powerful tools for nanoparticle manipulation and hence gains insight into biology phenomena and fundamental physics from molecular motor to protein folding 8, 9, 10, 11, 12, 13, 14. However, optical tweezing still faces the limitations of shallow penetration, low scale manipulation, complex devices and high laser power, which requires new efforts to seek other alternative technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, optical tweezing has been exploited as one of the most powerful tools for nanoparticle manipulation and hence gains insight into biology phenomena and fundamental physics from molecular motor to protein folding 8, 9, 10, 11, 12, 13, 14. However, optical tweezing still faces the limitations of shallow penetration, low scale manipulation, complex devices and high laser power, which requires new efforts to seek other alternative technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of chiral light with achiral objects has received much interest in the field of optical trapping and manipulation, leading to a high level of optomechanical control and detection at the micro and nanoscale [9][10][11][12][13] . The observation that light can transfer spin angular momentum (SAM) to matter dates back to the pioneering work by Beth 14 in 1936, who demonstrated that CP light exerts a torque on a birefringent wave plate.…”
mentioning
confidence: 99%
“…From quantum mechanics, CP light with angular frequency o carries both linear momentum (LM), :o/c, and SAM, s ± :, per photon with s þ ¼ þ 1 or s À ¼ À 1 for left-or right-handed CP, respectively 14 . The development of optical tweezers 15 (OT) stimulated the exploitation of optical forces and torques in several diverse areas such as biophysics 16 , nanotechnology 13 , complex fluids [17][18][19][20][21] , microrheology 10,11 and microfluidics 22,23 . In particular, several methods have been used to induce optically controlled rotations and alignment: anisotropic scattering due to particle shape 24,25 , form birefringence of anisotropic objects [26][27][28] , optical birefringence 9,12,29 and transfer of angular momentum (AM) from laser beams carrying SAM and/or orbital angular momentum 12,30,31 .…”
mentioning
confidence: 99%
“…There has been the use of spherical particles used as probes [Florin et al, 1997;Friese et al, 1999;Rohrbach et al, 2004;Volpe and Petrov, 2006;Volpe et al, 2007], as well as more bespoke devices [Carberry et al, 2010;Olof et al, 2012]. The use of bespoke probe particles for photonic force microscopy was reviewed in Maragò et al [2013]. Continuing the use of nonspherical shaped probe particles, led to the calibration of nonspherical probes in optical tweezers [Bui et al, 2013b;Grießhammer and Rohrbach, 2014].…”
Section: De Dtmentioning
confidence: 99%
“…The thermal statistics approach and related methods which involve thermal motion, have been explored for calibration in detail by Rohrbach's group (University of Freiburg, Germany) [Rohrbach et al, 2004], Ritsch-Marte's group (Innsbruck Medical University, Austria) [Singer et al, 2000], and also other groups who work with nonspherical probe particles, such as Marago's group (Istituto per i Processi Chimico-Fisici, Italy ) [Maragò et al, 2013] and the Bristol group (University of Bristol, United Kingdom) [Simpson and Hanna, 2012]. a b c Figure 2.3: Simulation of a spherical particle (polystyrene, 1 µm radius) undergoing a Brownian motion in a simulated Hookean trap, with κ = 0.025 N/m, and b a simulated optical trap, with wavelength 1064 nm, numerical aperture of 0.8, and power at the focus of 20 mW, and c free Brownian motion within the frame of the trapped particles.…”
Section: Boltzmann Statistics Analysismentioning
confidence: 99%